Development of an automatic fish feeder - Ozigbo, E.; Anyadike, C.; Gbadebo, F.; Okechukwu, R.U. (2013)
An automatic fish feeder was designed, fabricated and tested. It eliminates major problems associated with manual feeding in aquaculture. The machine was powered electrically by one horse power motor. The overall dimension of the machine is 62 × 45 × 45cm. The hopper carrying capacity is 5.5kg/volume of hopper with a variable discharging chute. The timer was designed with a 24hour time step at user's specified discharge duration. Test results at the discharge time of 60 minutes showed that 85.5kg of feeds were evenly distributed across the pond. Less than 3% feed loss was recorded due to breakage and fragile nature of feed. The machine has 86.9% efficiency and adequately manages and preserves feed under harsh conditions.